Link Between Menstrual Hygiene And Urinary Tract Infection - Thorat Sneha A,; Dr. Gaware Vinayak M,; GiteAnamika C, (Asian Journal of Pharmaceutical Research and Development, 2025)
Menstrual health problems affect a significant portion of the global female population, yet menstrual hygiene has long been overlooked as a critical public health concern. Menstrual health and hygiene (MHH) encompass not only the absence of disease but also the physical, mental, and social well-being associated with the menstrual cycle. Adolescent girls and women, particularly in low-resource settings, face challenges in maintaining proper menstrual hygiene due to limited access to water, sanitation, and hygiene (WASH) facilities, lack of affordable absorbent materials, insufficient education, and inadequate social support. These conditions increase the risk of reproductive tract infections (RTIs) and urinary tract infections (UTIs). Across different regions, menstrual hygiene practices are shaped by socioeconomic status, cultural beliefs, and educational background. In India, the reuse of cloths without proper cleaning especially in rural areas further elevates infection risks. Poor menstrual hygiene management (MHM), including inadequate sanitation, lack of private washing areas, and improper disposal of used materials, contributes to the spread of infections such as bacterial vaginosis (BV), RTIs, and UTIs. Promoting proper menstrual hygiene practices and improving access to menstrual health resources are essential to enhancing women’s overall reproductive health and reducing infection-related complications.